Clay barriers for embankment dams proceedings of the conference organized by the Institution of Civil Engineers, and held in London on 18 October 1989. (Thomas Telford, 1990)
Covers a range of recent developments in the design and construction of clay barriers for embankment dams and the interrelation between clay barriers and embankment and foundation designs.